Education and Sustainability, How SDG4 Contributes to Change the Representations of Developing Issues? The Case Study of Pakistan (International Journal of Management and Sustainability, 2020)
Every nation state is struggling hard to improve the living standard of its people so that Pakistan is looking for its people. It is believed that education can bring long lasting and sustainable transformation or change in any society towards better living standards and improve socio-economic conditions. There is consensus among the majority of nations and academia that quality education with inclusiveness and equity is the only tool which can bring a desired change. Education has a very close relationship with the contemporary paradigm shift of education for sustainable development to create critical thinking mindset of the nation to create healthy minds. Literature on sustainability and education demonstrates a causal link with socio-economic development. Academia, society, researchers, scientists, industry and all folks of society are convinced that education is the key tool to bring a change from local to global level in order to curtail contemporary challenges human beings and the planet is facing. A system analysis approach is used to understand logical links among loops. The causal relationship is demonstrated in the form of a Causal Loops Diagram (CLD) reinforces the idea that education is not only a key driver for introducing more sustainability into the development process, it is also a set of leverage points that should be gradually removed. Therefore, it is understood that quality education is affected by multiple factors to achieve.